Smartphone Use Type, Fear of Missing Out, Social Support, and Smartphone Screen Time Among Adolescents in Korea: Interactive Effects - Song, Hye-Young; Kim, Ji-Hye (Frontiers in Public Health, 2022)
This study aims to examine the relationship between intrapersonal factors, interpersonal factors, smartphone screen time, and the moderating roles of interpersonal factors, on the basis of the ecological model. This study is a cross-sectional and descriptive study. A total of 428 participants from four public middle schools were selected through convenience sampling (55.1% female; Mean age 13.0±0.78). Data were collected through self-report questionnaires that contained questions about sociodemographic characteristics, intrapersonal factors (types of smartphone use, Fear of missing out—FoMO), interpersonal factors (support from parents, teachers, and peers), and smartphone screen time. The collected data were analysed using descriptive statistics, t-test, ANOVA, Pearson’s correlation coefficients, and hierarchical regression. The daily smartphone screen time was 4.05±2.16 hours. Results showed that social media (β=.155), games (β=.140), and FoMO (β=.227) were positively associated with smartphone screen time, while educational videos (β=-.130) and parental support (β=-.212) were negatively associated with smartphone screen time. Peers support moderated the association between games and smartphone screen time. Parental support moderated the association between educational videos, videos/movies/TV and smartphone screen time. The findings highlight the direct and interactive roles of intrapersonal and interpersonal factors in predicting adolescents’ smartphone screen time. Based on this study, the intrapersonal and interpersonal factors of adolescents should be comprehensively considered to intervene in their proper smartphone use.